1994
DOI: 10.1042/bj2990219
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in the association and dissociation rate constants for binding of cystatins to target proteinases occurring on N-terminal truncation of the inhibitors indicate that the interaction mechanism varies with different enzymes

Abstract: The importance of the N-terminal region of human cystatin C or chicken cystatin for the kinetics of interactions of the inhibitors with four cysteine proteinases was characterized. The association rate constants for the binding of recombinant human cystatin C to papain, ficin, actinidin and recombinant rat cathepsin B were 1.1 x 10(7), 7.0 x 10(6), 2.4 x 10(6) and 1.4 x 10(6) M-1.s-1, whereas the corresponding dissociation rate constants were 1.3 x 10(-7), 9.2 x 10(-6), 4.6 x 10(-2) and 3.5 x 10(-4) s-1. N-Ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0
3

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 30 publications
8
105
0
3
Order By: Relevance
“…The crystal structure of human cathepsin B shows an additional loop, not present in papain, of about 20 amino acid residues, which partially occludes the active site. This loop was proposed to interfere with inhibitor binding [25], a suggestion supported by observations that the association rate constants for the interactions of inhibitors with cathepsin B are markedly lower than those for the binding to other enzymes [11,12,23].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The crystal structure of human cathepsin B shows an additional loop, not present in papain, of about 20 amino acid residues, which partially occludes the active site. This loop was proposed to interfere with inhibitor binding [25], a suggestion supported by observations that the association rate constants for the interactions of inhibitors with cathepsin B are markedly lower than those for the binding to other enzymes [11,12,23].…”
Section: Discussionmentioning
confidence: 84%
“…Three regions of the inhibitor were shown to interact with the enzyme: two hairpin loops and the N-terminal part [9,10], which appears to be more important in the cystatins [11][12][13].…”
mentioning
confidence: 99%
“…A structural element that has been shown to be at least partly responsible for the target enzyme specificity of cystatin C and of crucial importance for efficient cystatin C binding of cathepsin B is the N-terminal segment with ArgLeu-Val-Gly at positions 8 -11 (40,53). Leu-9 and Val-10, interacting with target enzyme substrate subpockets S 3 and S 2 , respectively, are especially important for a fast interaction between the cystatin and cathepsin B (54,55). The corresponding N-terminal segment in cystatin F is Val-Lys-Pro-Gly.…”
Section: Resultsmentioning
confidence: 99%
“…For fractionation of blood plasma, solid ammonium sulfate was added to a series of tubes containing 2-ml portions of plasma to achieve 25,30,40,45,50,55,60,70, and 75% (w/v) saturation. Following overnight incubation at 4°C, the tubes were centrifuged (10,000 ϫ g, 30 min), the supernatants were collected, and the precipitates were dissolved in water.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of the N-terminal region for the typical tight enzyme-binding property of cystatin C has previously been established [1,3,4]. We have shown that Leu-9 is the most discriminating residue for binding to cathepsins B, H, L and S, and thereby also a major determinant for the inhibitor's natural inhibition profile.…”
Section: Introductionmentioning
confidence: 92%